Medicinal Plants as Treatment for Common Symptoms of COVID-19 in Maibu Village, Butuan City, Philippines - Princess Kaye V. Palero; Francis Mar J. Solloso; Merrydel Grace Trinidad; Joel A. Mercado; Meljan T. Demetillo; Roger T. Sarmiento (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aimed to provide alternatives to pharmaceutical drugs by using knowledge of medicinal plants as a treatment for illnesses related to the symptoms of COVID-19. Forty traditional healers from the village were invited to serve as informants for this study. Their ages ranged from 50 to above, and those aged 60 had the highest number of informants. A total of 34 plant species belonging to 26 families and 33 genera have been reported as medicinal plants. The relative frequency of citation (RFC) values ranged from 0.525 to 0.025, with Plectranthus amboinicus being the highest (0.525). The use value (UV) ranged between 0.150 and 0.025, indicating a low range, as the study focused only on eight ailments related to COVID-19. Tree species constitute the largest portion of plants; leaves are the most utilized parts, and decoction is the most common method among traditional healers. This study proves that the knowledge and use of herbal medicine for the treatment of various ailments among local people is still a part of their life and culture.